Quantification of carpal tunnel morphology using centroid-to-boundary distance shape signatures. (May 2023) - Anderson, Drew A.; Oliver, Michele L.; Gordon, Karen D.
Highlights: Morphology analysis is valuable to understand carpal tunnel (CT) syndrome etiology. Previously published morphology methods may not fully capture the shape of the CT. This study details novel methods for 1-D shape signature representations of the CT. The methods captured morphology along the CT in greater detail than prior studies. Potential framework for further analysis of the CT or other anatomical structures. Abstract: Morphology analysis is valuable to understanding risk factors and the etiology of carpal tunnel (CT) syndrome. The objective of this study was to investigate morphology changes along the length of the CT using shape signatures (SS). Analysis was performed on ten cadaveric specimens in neutral wrist posture. Centroid-to-boundary distance SS were generated for proximal, middle, and distal CT cross-sections. Phase shift and Euclidean distance were quantified relative to a template SS for each specimen. Medial, lateral, palmar, and dorsal peaks were identified on each SS to generate metrics of tunnel width, tunnel depth, peak amplitude, peak angle. Width and depth measures were also performed using previously reported methods to serve as a basis of comparison. The phase shift revealed twisting of 21° between the ends of the tunnel. Distance from the template and width varied significantly over the length of the tunnel, while depth did not. Measures of width and depth using the SS method were consistent with previously reported methods. The SS method afforded the advantage of peak analysis with overall trends of peak amplitude indicating flattening of the tunnel at the proximal and distal ends relative to a rounder shape in the middle.